Northwest History. Alaska. Floods & Flood Control. (1937)
Torrent Engulfs Wilderness Post On Tanana River. Torrent Engulfs Wilderness Post On Tanana River FAIRBANKS, Alaska (/P)-Floods swept Fort Yukon on the Yukon river and Nenana on the Tanana river, sending torrents at least four feet deep through Fort Yukon and 14 yeet deep through Nenana, radiophone reports received here stated. No lives were reported lost. The, water was reported dropping slightly at Foirt Yukon, 150 miles northeast of here, and most of the danger past at Nenana, 50 miles southwest of Rairbanks. At Fairbanks, the Chena river was within its banks after causing heavy damage last week. Ray Randall, United States marshal's deputy at Fort Yukon, sent word by radiophone that most of the trading post was inundated when the Yukon river ice broke, but that damage apparently would not be extensive.